Produção e qualidade da forragem aproveitável de cultivares de guandu durante o período seco - FAVORETTO, V; Depaula, G. H.; Malheiros, E. B.; Guideli, C. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1995)
This work was carried out at Boa Esperanca Farm, sited in Jeriquara, Northeast of São Paulo State aiming to study seven cultivars of Pigeonpea (Cajanus cajan (L.) Millsp). Ramdomized blocks design were used in a split-plot scheme studying the following cultivars: Empasc 307, Fava Larga, Branco de Minas, ICPL 304, ICPL 85063, ICPL 270 and LGR 30, being the last four of them of Indian origin. Cultivars were cut three times during the period May-October, 1992. These cuts were done every twelve weeks, when leaves, flowers, pods and branches were harvested with diameter equal or smaller than 6 mm; the set of these fractions was considered available forage. Results showed that the cultivars, except Empasc 307, always revealed higher percentage of leaves and, consequently, higher dry matter production of this fraction in relation to total available forage. The available forage production, as well as the crude protein and acid detergent fiber percentage and in vitro dry matter digestibility allow to recommend the LGR 30, ICPL 304, Branco de Minas and ICPL 270 cultivars as the most promising ones for utilization as protein banks to be used during dry season.

O presente trabalho foi conduzido na Fazenda Boa Esperança, município de Jeriquara. região nordeste do Estado de São Paulo, com o objetivo de estudar a produção e a qualidade de sete cultivares de guandu (Cajanus cajan (L.) Millsp.). O delineamento utilizado foi de blocos casualizados, em esquema de parcelas subdivididas, estudando-se as seguintes cultivares: Empasc 307, Fava Larga, Branco de Minas, ICPL 304, ICPL 85063, ICPL 270 e LGR 30, sendo as quatro últimas de origem indiana. As cultivares foram submetidas a três colheitas, durante o período de maio a outubro de 1992, realizadas a cada doze semanas, quando se colhiam folhas, flores, vagens e ramos com diâmetro igual ou inferior a 6 mm, sendo o conjunto dessas frações denominado de forragem aproveitável. Os resultados mostraram que, com exceção da cultivar Empasc 307, as demais sempre revelaram maior percentual de folhas e, conseqüentemente, maior produção de matéria seca dessa fração, em relação à forragem aproveitável total. Em virtude da produção, bem como da composição de proteína bruta, da fibra em detergente ácido e da digestibilidade in vitro da matéria seca, as cultivares LGR 30, ICPL 304, Branco de Minas e ICPL 270 foram consideradas as mais promissoras na formação de bancos de proteína, para utilização durante o período seco.
Production and nutritive-value of the available forage of pigeon pea cultivars during dry season
Keywords: CHEMICAL COMPOSITION; DRY MATTER YIELD; LEAVES; CRUDE PROTEIN; Digestibility